Implementation and Evaluation of a Smart Uplink Jamming Attack in a Public 5G Network - Maya E. Flores; Devon D. Poisson; Colin J. Stevens; Adriyel V. Nieves; Alexander M. Wyglinski (IEEE Access, 2023)
In this paper, we present a hardware implementation and an evaluation of the effectiveness and feasibility of a smart jamming attack that targets specific uplink physical channels to destabilize 5G communication systems. Using software defined radio (SDR), we examine the susceptibility of the 5G Physical Uplink Shared Channel (PUSCH) to a smart jamming attack as well as the impact of such an attack on user equipment (UE) throughput. The smart jamming attack is designed to exploit the radio access procedure by: 1) identifying the user’s cell radio network temporary identifier (C-RNTI); 2) decoding the physical downlink control channel (PDCCH) information containing the specific UE resources; and 3) generating a quadrature phase shift keying (QPSK) modulated Orthogonal Frequency-Division Multiplexing (OFDM) waveform to effectively deny uplink access. A detailed description of the implementation of the overall testbed used to evaluate and quantify the effectiveness of the custom implementation of a smart jamming attack is presented in this paper. The evaluation results show that the smart jamming attack successfully denied uplink access by reducing the throughput of a specific UE by 100%.